2007
DOI: 10.1038/sj.bjc.6603688
|View full text |Cite
|
Sign up to set email alerts
|

The negative association between pre-eclampsia and breast cancer risk may depend on the offspring's gender

Abstract: If the negative association between pre-eclampsia and subsequent breast cancer risk differs by gender, this would strengthen the hypothesis that factors intrinsic to the particular pregnancy may explain the association. The study included 701 006 parous Norwegian women with follow-up for breast cancer through the Cancer Registry of Norway. Breast cancer risk was lower in women with pre-eclampsia/hypertension in their first pregnancy, compared to other women (relative risk, 0.86, 95% CI, 0.78 -0.94), after adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 11 publications
2
42
2
Order By: Relevance
“…Preeclampsia was associated with a modest, non-significant maternal breast cancer risk reduction overall (maternal ageadjusted OR ¼ 0.87) that was similar to Vatten et al's (2007) overall estimate (RR ¼ 0.86), but a marked and significant risk reduction among women who delivered their first infant after the age of 30 years (adjusted OR ¼ 0.33) ( Table 1). The overall association of preeclampsia to subsequent breast cancer risk did not differ by offspring gender (adjusted OR ¼ 0.86 vs 0.90 for women who delivered a son or a daughter, respectively).…”
Section: New York State-linked Birth and Tumour Registry Datamentioning
confidence: 74%
See 2 more Smart Citations
“…Preeclampsia was associated with a modest, non-significant maternal breast cancer risk reduction overall (maternal ageadjusted OR ¼ 0.87) that was similar to Vatten et al's (2007) overall estimate (RR ¼ 0.86), but a marked and significant risk reduction among women who delivered their first infant after the age of 30 years (adjusted OR ¼ 0.33) ( Table 1). The overall association of preeclampsia to subsequent breast cancer risk did not differ by offspring gender (adjusted OR ¼ 0.86 vs 0.90 for women who delivered a son or a daughter, respectively).…”
Section: New York State-linked Birth and Tumour Registry Datamentioning
confidence: 74%
“…If the findings of Vatten et al (2007) and what we observe in the present study among older mothers of male preeclamptic pregnancies are real, characterising the hormonal profile of preeclamptic pregnancies by fetal gender and maternal age may provide additional insight into the mechanisms underlying the apparent protective effect of preeclampsia.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, a recent meta-analysis reported a 14% reduced risk of breast cancer in women with a history of preeclampsia (HR ¼ 0.86 [95% CI 0.71e1.01]) [5]. Some studies suggest that such risk reduction is conferred to preeclamptic pregnancies with a male fetus only [6]. To further characterize the association between preeclampsia and breast cancer, in the current study we investigated the association overall and according to birth characteristics using nationwide Danish register-based data.…”
Section: Introductionmentioning
confidence: 94%
“…As women who smoke are less likely to develop pre-eclampsia, it has been suggested that women who had pre-eclampsia are less likely to develop cancer. 76 Systematic review and meta-analysis shows that this does not appear to be true. 25 Cigarette smoke may protect from pre-eclampsia through the action of carbon monoxide on the haemeoxygenase system, which in turn has been shown to lower production of sFlt-1 and sEng from endothelial cells and placental trophoblast.…”
Section: Pre-eclampsia Smoking and Future Cancermentioning
confidence: 99%